(untitled) (Veterinary Science, 2017)
The authors present an infrequent case of chondrosarcoma in a horse and its special evolution in reponse to our treatment. A ten-year-old male horse weighing 480 kg showed a neoplastic formation on the anterior lateral and median fece of III metatar.sal bone, with a lobular shape, yellowish-white colour, firm consistency, of chondroid type, lacking granu1ation tissue and epidermis and wich was 5 months old. The horse had a case recordof sharp injuries near the lesion produced by wire, and the owner had applied lime on the injuries. The tumour was sugically removed, it weghed 14 kg and samples were taken for a histopathological study. Relapse occurred after 20 days. The tumour was removed again and 5 fluorouracilo was applied to the surgical area once a week during 6 weeks. After 9 monsths, the horse showed clinical impairment and weight loss, so it is treated with an extract of Uncaria tomentosa IV in 30 ml d.oSes, 3 times a week. The horse died a year later after the second operation